Malabar and the portuguese - "Panikkar, K. M" (New Delhi, 1997)
It was possible for the Portuguese to accomplish what they managed to do, as, when Vasco da Gama reached the Malabar Coast the country was split up into petty principalities over whom no one had any real authority not even the Zamorin of Calicut. So it did not require any particular political insight to playoff the princelings along the coast against each other and establish foreign authority over small isolated coastwise areas.
Keywords: Histoty-Kerala-Malabar